Respon Biologis Pemberian Bungkil Kelapa Hasil Fermentasi dengan Trichoderma harzianum dalam Ransum Terhadap Performans Ayam Pedaging - Mairizal, Mairizal; Erwan, Edi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
The  experiment  was  aimed  to  see  the  effect  of  coconut  cake  fermentation  with Trichoderma Harzianum (TH) in ration on the performance of male broiler. 100 heads of three-day-old broiler chiken were  arranged  to  completely  randomized  treatment  with  5  kinds  of  ration  such  as  0%,  5%,  10%,  15% and  20  %  of  coconut  cake  fermentation  with  TH  and  4  times  replication.  Data  collected  were  feed consuption, body weight gain and feed conversion. Analisys of variance and Duncan’s multiple range test were used to analize the data. The result showed that the use of coconat cake fermentation with TH significantly (P<0,05) reduced body weight gain, but there was no effect (P>0,05) on feed consumption and  feed  conversion.  From  the  experiment  result  we  concluded  that  only  15  %  of  coconut  cake fermentation with TH which can be suggested in male broiler chiken ration